Morphological and molecular identification of amphistomes of wild ruminants from selected conservancies of Matebeleland region of Zimbabwe - Madeline Siyazisiwe Sibula; Mokgadi Pulane Malatji; Ignore Nyagura; Pinky Ndlovu; Thulani Jele; Mukhululi Ndlovu; Samson Mukaratirwa (International Journal for Parasitology: Parasites and Wildlife)
Amphistomosis is a poorly understood trematode disease of domestic and wild ruminants whose effect has been underestimated. To date, there is limited information on the taxonomic status of amphistome species, particularly in sub-Saharan Africa which is home to diverse species infecting domestic and wild ruminants. In view of this, a survey was conducted in wildlife conservancies and national parks located in Beitbridge, Nyamandlovu, and Hwange in the Matebeleland region of Zimbabwe during the 2019–2021 game hunting seasons. Gastrointestinal tract of 329 carcasses of wild ruminants were examined for amphistome infections and 33/329 (10 %) of the animals were infected and the highest prevalence per locality was in Hwange (35 %; 7/20). A high prevalence of 63 % was recorded in Kobus ellipsiprymnus (waterbuck) from Beitbridge, accompanied with a high parasitic burden of more than 10 000 parasites per animal. The lowest parasitic burden was observed in Connochaetes taurinus taurinus (blue wildebeest) and Hippotragus niger (sable), each with less than 10 amphistomes. A total of 86 amphistome specimens from Syncerus caffer (African buffalo) (n = 27), Aepyceros melampus (impala) (n = 17), Tragelaphus strepsiceros (kudu) (n = 16), waterbuck (n = 10), sable (n = 7), Redunca arundinum (reedbuck) (n = 7), and Connochaetes taurinus taurinus (blue wildebeest) (n = 2) were randomly selected for morphological and molecular identification. Using a combination of both histological technique and ITS-2 rDNA marker, the following seven amphistome species were identified; Leiperocotyle (L.) gretillati, Calicophoron (C.) microbothrium, C. raja, C. clavula, C. phillerouxi, Gigantocotyle (Gi.) symmeri, and Gastrothylax (G.) crumenifer which are pouched amphistome species. Orthocoelium dicranocoelium identification was based on morphological characters only. Although the ITS-2 is a widely used marker, it may not be useful in discriminating cryptic species in the Calicophoron genus. Orthocoelium (O.) dicranocoelium, G. crumenifer and L. gretillati are first records in wild ruminants in Zimbabwe.